Ammonia Oxide as a Building Block for High‐Performance and Insensitive Energetic Materials. Issue 21 (24th April 2017) - Tang, Yongxing; Mitchell, Lauren A.; Imler, Gregory H.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract: 3, 5‐Dinitrimino‐1, 2, 4‐triazole (2 ) with three protons has the potential of deprotonation to form energetic salts. Neutralization of2 with 50 % hydroxylamine in varying molar ratios leads to the formation of the corresponding mono/dihydroxylammonium energetic salts. Additionally compound5, an ammonia oxide adduct of dihydroxylammonium 3, 5‐dinitramino‐1, 2, 4‐triazolate, was prepared when excess hydroxylamine was used. The structures of3 –5 are supported by single‐crystal X‐ray diffraction. The energetic properties of the new materials are competitive. Utilization of ammonia oxide adducts in hydroxylammonium energetic salts could lead to future practical applications as energetic materials. Abstract : Hydroxylammonium salts of 3, 5‐dinitramino‐1, 2, 4‐triazolate (DNT) have been prepared. The ammonia oxide (NH3 O) adduct of the dihydroxylammonium salt of DNT (see structure) can be employed as a building block to enhance energetic performance and decrease sensitivity.